Main factors affecting climate change, acidification and eutrophication in MSW management systems - Lombardi, Lidia; Cipriano, Luca; Carnevale, Ennio; Havukainen, Jouni; Liikanen, Miia; Hupponen, Mari; Horttanainen, Mika (ECI Digital Archives, 2016)
The continuous increasing of solid waste generation worldwide calls for management strategies to support environmental sustainability. Life Cycle Assessment (LCA) is a decision-support tool for quantifying environmental impacts of systems (product systems). Among the most important and discussed output-based impact categories of waste management, there are: global warming potential (GWP), acidification potential (AP) and eutrophication potential (EP). The aim of this work is to identify which are the most important factors in the Municipal Solid Waste (MSW) management affecting to GWP, AP and EP and what kind of conditions in the operating environment are essentials to these factors. After a review of available literature on this topic (more than thirthy rarther recent papers were analyzed in details even if the reference list is not reported here for length constraints), the work was concentrated at evaluating two rather different study cases: i) the territory belonging to the province of Siena in the south of Tuscany region (Italy) and ii) the territory of South Karelia, the region in the southern Finland on the border with Russia. The total amount of MSW generated in the province of Siena in 2013 was 163 823 t, of which 94 963 t are residual waste, which is processed in a mechanical and biological treatment (MBT) plant. Dry fraction from MBT is sent for waste-to-energy (WtE), while humid fraction is landfilled after aerobic biological stabilization. Source separated wastes (about 45%) are refined locally by mechanical treatment and sent away for material recovery, in particular the organic fraction is processed locally for compost production. Concerning South Karelia region, the total amount of MSW generated in 2013 was 75 280 t, of which 22 500 t are residual waste. Separate collection is reserved for recoverable materials (cardboard, glass, metal, and paper) as well as for biodegradable waste. Residual urban waste is partly disposed to landfill and partly burned into WtE plant. Landfilling has been the only ...